How and when servant leadership affect public employees’ innovative behavior - Fen-Xian Xiao; Yun Lin; Jun-Feng Kuang; Lin-Lin Yang; Qiu Wang (Scientific Reports)
Abstract Drawing on job demands–resources theory, this study explains the underlying mechanism by which servant leadership affects public employees’ innovative behaviors. Building upon this foundation, the study constructs a hypothesized theoretical model positioning psychological safety as the mediator and public service motivation as the moderator. Through institutional cooperation with graduate schools at two universities in Yunnan Province, China, a survey was administered to 680 Master of Public Administration students, yielding 642 valid responses for analysis. Based on a sample of 642 public employees from public organizations in China, servant leadership was found to positively affect public employees’ psychological safety and innovative behaviors. Psychological safety partially mediated the relationship between servant leadership and innovative behaviors. Furthermore, public service motivation moderated the link between psychological safety and innovative behaviors. These findings suggest that public organizations must develop and train servant leaders using various strategies to establish and maintain a psychologically safe work environment conducive to innovation and also should attach importance to the significant role of public service motivation in enhancing innovative behaviors among public employees.